Determinants associated with making prenatal screening decisions in a national study. (2nd January 2019) - Bakst, Shelly; Romano-Zelekha, Orly; Ostrovsky, Jenny; Shohat, Tamy
Abstract: This study sought to evaluate the associations between background exposures and psychological determinants, among postpartum Jewish and Arab women, relative to actual prenatal test endorsement. The independent and aggregative effects of contextual features and the subjective opinions and attitudes relative to a prenatal testing were evaluated, using logistic regressions. After accounting for contextual features, Jews with positive vs. negative opinions on screening were significantly more likely to undergo a prenatal screening. Specifically, having more favourable ideas on pregnancy termination, among Jews, was associated with a greater likelihood of triple test, nuchal translucency and ultrasound uptake as compared with those that refused. Similarly, Arabs who were more inclined to abort the pregnancy had a greater chance of using nuchal translucency and ultrasound vs. those that declined testing. As the preferences for prenatal test outcomes are multifaceted and vary according to population group, a better understanding of the factors involved in making testing choices could help ease the decision-making process. Impact Statement: What is already known on this subject? The choice to undergo prenatal screening tests is influenced by various determinants, which include: social, demographic and emotional factors that vary by cultural preferences. Indeed, women integrate (subjective) beliefs and values that extend beyond rational (objective) reasoning when estimating whether or not to undergo testing. It may then be that, prenatal test choices might be, influenced less by actual risk status and more so by emotional factors. And while, the latter are more likely to be amendable, and thus influence changes in perception, the effect of psychological exposures on the decision making process in the genetic testing context, especially among Israeli Jews and Arabs, has been understudied. What the results of this study add? The current study extends the focus by addressing the role of evaluative beliefs and emotional factors involved with formulating prenatal screening judgments relative to actual testing among individuals with diverse profiles (Israeli Jews and Arabs). What was clarified was that background factors and psychological perceptions, such as having supportive attitudes on screening and a willingness to undergo abortion were, for the most part, related to prenatal test uptake. Concomitantly, these involve dense decision-making practices that can be difficult to approximate, as cultural settings and individual preferences often have an impact on intention-to-test. What the implications are of these findings for clinical practice and/or further research? Culturally appropriate counselling that would account for personal preferences alongside actual risk appraisals could enable pregnant women to make informed and autonomous prenatal testing choices. The integration of socio-demographics, psychological correlates and other contextual factors into a theoretical framework, studied uniquely by sub-populations, could enrich future research. Such research can, in turn, provide a clearer picture of the social need for genetic counselling, help customise local interventions, and on a broader scale inform national policy.